2005
DOI: 10.1111/j.1365-2249.2005.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ CD25+ T cells with the phenotypic and functional characteristics of regulatory T cells are enriched in the synovial fluid of patients with rheumatoid arthritis

Abstract: Summary CD4+ CD25+ + + + regulatory T (T reg ) cells play a critical role in the maintenance of peripheral tolerance and the prevention of autoimmunity. In the present study, we have explored the characteristics of CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
190
0
27

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 283 publications
(241 citation statements)
references
References 47 publications
15
190
0
27
Order By: Relevance
“…This evidence supports the idea that a deficiency of this cell subset may be a possible factor in susceptibility to RA [42]. This hypothesis seems to be further supported by investigations of the correlation between the percentage of Treg cells in PB and disease duration, which have confirmed higher numbers of circulating Treg cells in patients with long-standing disease [35,39]. Moreover, in established disease, where proinflammatory cytokines, including TNFα, are present at high levels in PB and target organs, FoxP3 expression within the CD4 + CD25 + cell population seems to be reduced, giving rise to the hypothesis that proinflammatory molecules play a role in inducing an abnormal Treg cell phenotype [37,40].…”
Section: The Paradox Of Treg Cell Expansion In Ra Patientssupporting
confidence: 84%
See 2 more Smart Citations
“…This evidence supports the idea that a deficiency of this cell subset may be a possible factor in susceptibility to RA [42]. This hypothesis seems to be further supported by investigations of the correlation between the percentage of Treg cells in PB and disease duration, which have confirmed higher numbers of circulating Treg cells in patients with long-standing disease [35,39]. Moreover, in established disease, where proinflammatory cytokines, including TNFα, are present at high levels in PB and target organs, FoxP3 expression within the CD4 + CD25 + cell population seems to be reduced, giving rise to the hypothesis that proinflammatory molecules play a role in inducing an abnormal Treg cell phenotype [37,40].…”
Section: The Paradox Of Treg Cell Expansion In Ra Patientssupporting
confidence: 84%
“…47 Autoimmun Since phenotypic characterization does not allow a definite conclusion as to whether expanded CD4 + CD25 high T cells in the SF are actually Treg, the most convincing evidence is undoubtedly provided by in vitro functional studies. Suppressive activity of CD4 + CD25 high T cells in the SF has been confirmed in some studies by coculture with autologous effector T cells [33][34][35][36][37][38][39]. In contrast, some authors have demonstrated a reduced suppressive activity of Treg cells in PB from RA patients, that can be restored by adequate pharmacological therapy, as discussed in detail below (see Table 2).…”
Section: The Paradox Of Treg Cell Expansion In Ra Patientsmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, the outcome of the local T cell response (condition 5) will depend on the site and environment of T cell triggering (SF, ST, or draining lymph nodes, with each site containing various cytokines), T cell receptor affinity for the antigen (37), and ratio of antigen-specific effector T cells and Treg cells (38)(39)(40). Peripheral HC gp-39-specific T cells have been observed in both RA patients (5,7,41) and healthy controls (42).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals these cells may have a role in preserving natural immune homeostasis, a function that is suppressed in RA (42). However, so far, the presence of functional HC gp-39-specific T cells in SF has been difficult to detect, possibly due to local T cell exhaustion or suppression (37)(38)(39)(40)42,43).…”
Section: Discussionmentioning
confidence: 99%